Perforated Subhepatic Appendicitis: A Case Report - Muhamad Hud Muhamad Zin; Nik Ritza Kosai; Firdaus Hayati (Gazi Universitesi, 2021)
Acute appendicitis is among common surgical emergency. Subhepatic appendicitis is rare and difficult to diagnose and manage. A 59 year’s old lady with no known medical illness presented with undifferentiated right abdominal pain. Difficulties come upon diagnosis and management due to retrocecal subhepatic appendix mal location. Subhepatic appendicitis is a rare occurrence and its infrequent location makes it difficult to diagnose. Awareness of various location of appendix, a high index of suspicion and radiological imaging is required for prompt diagnosis and management